KORELASI KEBIASAAN MEMBACA TERHADAP POSTUR TUBUH SISWA SMA - Diyono, Diyono; Awanis, Almas; Setyoningsih, Titi (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Reading habits are an important activity for adolescents, but reading practices that do not pay attention to ergonomic aspects can affect posture quality. This study aims to analyze the relationship between reading habits and the posture of high school students. The research design used is descriptive analytical with a cross-sectional approach. The sample consisted of 36 high school students aged 15–16 years old from Surakarta who were selected purposively. Data on reading habits, including duration, frequency, position, lighting, and media, were collected through questionnaires, while posture was assessed using the New York Posture Rating Scale (NYPRS). Descriptive analysis was used to describe the distribution of data and the relationship between variables. The results showed that most students read using gadgets (61.1%) while sitting on a chair (33.3%) or lying down (33.3%). The average posture score was 82.63, which was categorized as fairly good. However, lying down and lying on the stomach, as well as dim lighting, were associated with lower posture scores. These findings confirm that non-ergonomic reading habits can increase the risk of musculoskeletal disorders in adolescents. The implication of this study is the importance of reading ergonomics education for students, teachers, and parents, as well as improving learning facilities that support healthy posture to prevent musculoskeletal problems from an early age. Keywords: Reading habits, Body posture, Adolescents.